Analisis Pemanfaatan Dana Desa Dalam Pelaksanaan Pembangunan Di Desa Tafuli I Kecamatan Rinhat, Kabupaten Malaka - Vidensia Bergita Anin (Jurnal Administrasi Terapan, 2024)
Research with the title: "Analysis of the Use of Village Funds in Implementing Development in Tafuli I Village, Rinhat District, Malaka Regency." The objectives of this research are: (1) Knowing the use of Village Funds in implementing development (2) Knowing the factors that support the use of village funds in implementing development in Tafuli I Village, (3) Knowing the inhibiting factors in utilizing Village Funds, ( 4) Find out the effectiveness of what has been done in utilizing village funds in implementing development in Tafuli I Village, Rinhat District, Malaka Regency. This research uses a qualitative descriptive method. Data collection techniques were carried out by means of observation, interviews and documentation. The research results show that: (1) The use of Village Funds in implementing development in Tafuli I Village has been used for physical development activities, (2) Supporting factors for the utilization of Village Funds in Tafuli I Village are shown through community participation during road construction activities. (3) Factors inhibiting the utilization of Village Funds in Tafuli I Village, Rinhat District, Malacca Regency, include; low capacity of the community in proposing types of needs during the Village Musrembang, slow disbursement of Village Funds, low community participation and involvement during the Village Musrembang, minimal outreach activities from the village government regarding utilization including the function and use of Village Funds, low monitoring and control activities by the Regional government and the village community itself, as well as the occurrence of situational natural disasters. (4) Effective use of village funds is very effective for physical development